2004
DOI: 10.1074/jbc.m310044200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Positive Transcription Elongation Factor b (P-TEFb) Is Tagged for Inhibition through Association with 7SK snRNA

Abstract: The positive transcription elongation factor b (PTEFb), comprising CDK9 and cyclin T, stimulates transcription of cellular and viral genes by phosphorylating RNA polymerase II. A major portion of nuclear P-TEFb is sequestered and inactivated by the coordinated actions of the 7SK snRNA and the HEXIM1 protein, whose induced dissociation from P-TEFb is crucial for stressinduced transcription and pathogenesis of cardiac hypertrophy. The 7SK⅐P-TEFb interaction, which can occur independently of HEXIM1 and does not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
216
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(223 citation statements)
references
References 40 publications
6
216
1
Order By: Relevance
“…Overexpression of PPM1A and PPM1B also greatly reduced the amount of the HEXIM1 protein that co-immunoprecipitated with FLAG-Cdk9. The reduction in HEXIM1 associated with Cdk9 was expected as the association of HEXIM1 and 7SK RNA with P-TEFb requires phosphorylation of Thr-186 in the Cdk9 T-loop (21). We also observed in another co-immunoprecipitation experiment that overexpression of PPM1A reduced the association of 7SK RNA and HEXIM1 with a transfected FLAG-Cdk9 protein (data not shown).…”
Section: Specificity Of Antiserum Against Phosphorylated Cdk9supporting
confidence: 56%
See 1 more Smart Citation
“…Overexpression of PPM1A and PPM1B also greatly reduced the amount of the HEXIM1 protein that co-immunoprecipitated with FLAG-Cdk9. The reduction in HEXIM1 associated with Cdk9 was expected as the association of HEXIM1 and 7SK RNA with P-TEFb requires phosphorylation of Thr-186 in the Cdk9 T-loop (21). We also observed in another co-immunoprecipitation experiment that overexpression of PPM1A reduced the association of 7SK RNA and HEXIM1 with a transfected FLAG-Cdk9 protein (data not shown).…”
Section: Specificity Of Antiserum Against Phosphorylated Cdk9supporting
confidence: 56%
“…Cyclin-dependent kinases contain a conserved threonine in their T-loop, and phosphorylation of this residue induces a conformational change that allows Cdk substrates to access the catalytic core of the enzyme (19,20). In the case of Cdk9, the association of 7SK with P-TEFb has been shown to be dependent on Thr-186 phosphorylation (21). A recent study reported that under conditions of stress, either UV irradiation or treatment with high concentrations of hexamethylene bisacetamide, the phosphatases PP2B and PP1␣ act cooperatively to disrupt P-TEFb from the 7SK small nuclear ribonucleoprotein through the dephosphorylation of Thr-186 (22).…”
mentioning
confidence: 99%
“…These two mechanisms share similar regulatory logistics and cooperate in part by influencing the activity of the binding sites in target genes. Some lncRNAs, such as 7SK, can directly affect the loading and activity of general TFs and to further affect the production of mRNAs[54]. Moreover, another lncRNA, NRON, can directly serve as either co-factors or inhibitors to regulate the activity of nuclear factor of activated T cells (NFAT) proteins which manipulate gene expression in many cell types[55].…”
Section: Discussionmentioning
confidence: 99%
“…CmRBP50 C-terminal Phosphorylation Is Necessary for Interaction with Phloem Proteins-RNA-binding protein phosphorylation has recently been reported as a requirement for RNP complex formation (37,38). To further investigate the role of CmRBP50 phosphorylation in protein-protein interaction, we next conducted co-IP and protein overlay assays using proteins contained within pumpkin phloem sap (30,35,39) (Fig.…”
Section: Resultsmentioning
confidence: 99%